Junction formation of Cu 3BiS 3 investigated by Kelvin probe force microscopy and surface photovoltage measurements (2012)
Recently, the compound semiconductor Cu3BiS3 has been demonstrated to have a band gap of ~1.4 eV, well suited for photovoltaic energy harvesting. The preparation of polycrystalline thin films was successfully realized and now the junction formation to the n-type window needs to be developed. We present an investigation of the Cu3BiS3 absorber layer and the junction formation with CdS, ZnS and In2S3 buffer layers. Kelvin probe force microscopy shows the granular structure of the buffer layers with small grains of 20–100 nm, and a considerably smaller work-function distribution for In2S3 compared to that of CdS and ZnS. For In2S3 and CdS buffer layers the KPFM experiments indicate negatively charged Cu3BiS3 grain boundaries resulting from the deposition of the buffer layer. Macroscopic measurements of the surface photovoltage at variable excitation wavelength indicate the influence of defect states below the band gap on charge separation and a surface-defect passivation by the In2S3 buffer layer. Our findings indicate that Cu3BiS3 may become an interesting absorber material for thin-film solar cells; however, for photovoltaic application the band bending at the charge-selective contact has to be increased.